1998
DOI: 10.1111/j.1600-0528.1998.tb01981.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of dental aesthetics in the United States and Nigeria

Abstract: The standard dental aesthetic index (DAI) is an orthodontic treatment need index based on perceptions of dental aesthetics in the United States. It is a regression equation that links perceptions of the social acceptability of dental aesthetics with the objective intraoral measurements of ten occlusal traits. For the index to be universally acceptable, the perceptions of dental aesthetics in other countries must be similar to those of the United States. This study was designed to determine whether the percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 11 publications
3
19
0
6
Order By: Relevance
“…[25] Most participants in this study felt that their oral health had an effect, mostly a good or very good effect on their QoL, similar to earlier studies from developed countries. [34,35] Studies conducted in Nigeria have also reported that there appear to be a shortage in the number of practicing dentists, [36] and the involvement of physicians untrained in oral health care providing dental services.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…[25] Most participants in this study felt that their oral health had an effect, mostly a good or very good effect on their QoL, similar to earlier studies from developed countries. [34,35] Studies conducted in Nigeria have also reported that there appear to be a shortage in the number of practicing dentists, [36] and the involvement of physicians untrained in oral health care providing dental services.…”
Section: Discussionsupporting
confidence: 79%
“…[24] Overall, their perception of the importance of dental health was similar to those reported from the United States. [25] In a recently published study conducted in Nigeria we demonstrated that being younger, being female, and being employed were associated with visiting a dentist in the past 12 months. [26] Other studies have documented prevalence of dental caries and periodontal disease in Nigeria, [27] and described oral health care practice among physicians, [28] as well as oral health knowledge and attitudes of Nigerian school teachers.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmed et al [14] reported that children from black ethnic minorities were more likely to perceive less need for treatment compared to professional assessment. In contrast, Otuyemi et al [19] showed no difference in the perceptions of dental aesthetics between adult Nigerians and Americans.…”
Section: Discussionmentioning
confidence: 97%
“…3 There is no nation free from oro-dental diseases, but the pattern of prevalence of the diseases vary from country to country. [3][4][5]7,10 Oral hygiene mainly depends on the knowledge of the people. In students, the knowledge and practice of oro-dental hygiene can be raised through child to child education.…”
Section: Introductionmentioning
confidence: 99%